PENGEMBANGAN MEDIA ULAR TANGGA MATEMATIKA TERHADAP KEAKTIFAN BELAJAR SISWA PADA MATERI PENJUMLAHAN DAN PENGURANGAN BERSUSUN - Aulia Ratnasari; Jasiah (AL JABAR: Jurnal Pendidikan dan Pembelajaran Matematika, 2026)
Abstract This study aims to develop a mathematical snakes and ladders game and test its impact on the learning activity of fourth-grade students at MIN 1 Palangka Raya on the subject of addition and subtraction. The main problem found was the low learning activity of students, most of whom (around 70%) had a kinesthetic learning style due to the use of conventional learning methods and the lack of attractive media. The type of research used was Research and Development (R&D) with a 4D development model: Define, Design, Development, and Disseminate. The research subjects were 28 fourth grade students at MIN 1 Palangka Raya. The mathematical snake and ladder media was developed as an interactive and fun educational game. The results showed that the implementation of the mathematical snake and ladder media in learning had a positive and effective impact on stimulating students' interest and activity in learning. Students became more enthusiastic, actively discussed in groups, engaged in problem solving, and were motivated to learn while playing. This shows that the mathematical snake and ladder media is in line with the characteristics of students' kinesthetic learning styles.